In vitro repellent effect of tea tree (melaleuca alternifolia) and andiroba (carapa guianensis) oils on haemotobia irritans and chrysomya megacephala flies - Klauck V.* (2015)
© 2015, Malaysian Society for Parasitology. All rights reserved.This study aimed to evaluate the repellent effect of tea tree (Melaleuca alternifolia) and andiroba (Carapa guianensis) essential oils on two species of flies (Haemotobia irritans and Chrysomya megacephala). For the in vitro studies, free-living adult flies were captured and reared in the laboratory. To verify the repellency effect, an apparatus was constructed where H. irritans and C. megacephala were exposed to andiroba and tea tree oils (5.0%), as well as to a known repellent (citronella, 5.0%) to validate the test. The study demonstrated that all three oils used showed in vitro repellent effect against both species of flies. It is possible to conclude that the essential oils (tea tree and andiroba) have repellent effect on these species of flies used in this study.